ENTREPRENEURSHIP COMPETENCE OF THE PRINCIPAL IN IMPROVING SCHOOL INDEPENDENCE IN SD MUHAMMADIYAH KLECO 2 KOTAGEDE YOGYAKARTA - Syapriyuda, Sandy; Santosa, Achadi Budi (International Journal of Educational Management and Innovation, 2020)
The purpose of this study is to know : (1). entrepreneurship competencies of the principal of SD Muhammadiyah Kleco 2 Kotagede Yogyakarta. (2). programs that carried out by school principals in developing school potential, and (3) the competence of principals increases school independence. This research uses a qualitative approach. Data collection is done by observation, in-depth interviews, and documentation studies. Conclusions are drawn in a variety of extrapolations based on the reliability of research findings. While the validity of the data is carried out in terms of credibility, transferability, and confirmation. The results of the study are as follows (1). The principal of the Muhammadiyah Kleco 2 Elementary School has good entrepreneurial competence, as evidenced by (a). innovations made. (b). work hard to achieve school success. (c). strong motivation for success. (d). always looking for the best solution in facing obstacles faced by schools. (e). The principal has an entrepreneurial instinct in managing school activities as a source of learning for students (2). Able to plan and run school programs and develop school potential. (3). Able to increase school independence.